Design of an intelligent transformer oil sampling system - Shaotong Pei; Haichao Sun (Electronics Letters, 2023)
Abstract In response to the transformer oil sampling requirements within substations, this paper presents the design and development of a highly intelligent transformer oil sampling system. The robot employs a tracked mobile chassis and a gantry robotic arm, offering high mobility stability and operational reliability. The system effectively conducted oil sampling operations in an extra‐high voltage substation, obtaining valuable oil samples that validate the structural and functional reliability of the system, as well as its stability in complex working environments. This research provides a promising solution for transformer maintenance and health monitoring, with the potential to play a significant role in power equipment maintenance.